2005
DOI: 10.1007/s10620-005-1612-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moxibustion at Acupoints Ren-12 (Zhongwan), St-25 (Tianshu), and St-36 (Zuzanli) in the Prevention of Gastric Lesions Induced by Indomethacin in Wistar Rats

Abstract: This study was aimed at assessing the physical characteristics underlying the action of moxibustion at acupoints Ren-12 (Zhongwan), St-25 (Tianshu), and St-36 (Zuzanli) in preventing acute injuries of the gastric mucous membrane induced by indomethacin in Wistar rats. Induction of gastric lesions, by means of intragastric administration of indomethacin (100 mg/kg), in adult male Wistar rats was followed by treatment with moxibustion using Artemisia vulgaris dried leaves at 60 or 45 degrees C, heating with Arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Scientific advances have clarified the neurobiological basis of both EA and MO, mainly through experimental models using EA at the acupoint ST-36 [27,63]. To our knowledge, our work was the first to use EA at both ST-36 and KI-3 combined with MO in BL-23.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientific advances have clarified the neurobiological basis of both EA and MO, mainly through experimental models using EA at the acupoint ST-36 [27,63]. To our knowledge, our work was the first to use EA at both ST-36 and KI-3 combined with MO in BL-23.…”
Section: Discussionmentioning
confidence: 99%
“…A number of papers studying different animal species have clearly shown that the location of acupuncture points follows a similar distribution in these mammals [25]. The entire treatment consisted of 16 sessions over the course of 8 weeks (20-min sessions, twice weekly) [26,27], under inhalatory anesthesia. The needle used for stimulation was 0.25 mm in diameter, 2 cm long and had a stainless steel stem and copper handle.…”
Section: Methodsmentioning
confidence: 99%
“…Several previous studies have assessed the effect of moxibustion [77][78][79][80], but quantification of the effects of moxibustion has been difficult because the temperature of application and the temperature distribution are not uniform. Moxibustion is the way of heating a local area in which moxa is burned at acupoints on the skin.…”
Section: Moxibustion and Heat Transfer Control Device (Htcd)mentioning
confidence: 99%
“…As stated above, reproducibility is the challenge for this type of moxibustion experiment. Several studies have assessed the effect of moxibustion (Freire et al, 2005;Joos et al, 2004;Joos et al, 2006;Yun et al, 2007), but controlling the temperature achieved by burning moxa has been difficult. The actual temperature depends on the practitioner's experience, and the temperature distribution in the target area is not uniform, making quantification of the effects of moxibustion difficult.…”
Section: Reproducible Simple or Standardised Intervention For The Acumentioning
confidence: 99%